Content and Face Validity of Religious Conditionality in Conditional Cash Transfers for Zakat Distribution - Mohamed Esa, Mohd Suffian; Salmy Edawati Yaacob; Hairunnizam Wahid; Amir Fazlim Jusoh (Universitas Islam Negeri Raden Intan Lampung, 2025)
Despite the increasing distribution of zakat in Malaysia, its effectiveness in alleviating poverty remains limited, partly due to unproductive behaviors among recipients. Simultaneously, current Conditional Cash Transfer (CCT) programs lack long- term sustainability. Integrating religious conditionality into zakat-based CCT models may address these limitations. This study aims to evaluate the content and face validity of religious conditionality items developed from a comprehensive literature review. A total of 12 items were assessed by 10 experts using established validation methods. Content validity was evaluated using the Content Validity Index (CVI), Kappa statistics, and Content Validity Ratio (CVR), while face validity was measured through expert agreement on item relevance and clarity. The findings indicate that the RC-ZCCT scale has strong content and face validity. I-CVI scores ranged from 0.90 to 1.00, with S-CVI scores of 0.975 (relevance) and 0.950 (clarity). Kappa statistics also ranged from 0.90 to 1.00, and CVR values from 0.80 to 1.00, all exceeding accepted thresholds. Face validity results showed expert agreement ranging from 90% to 100%, with an overall agreement of 96%, confirming the appropriateness of the items. Minor revisions were made based on expert feedback, but all items were retained. The validated RC-ZCCT scale presents a reliable instrument for developing zakat-based interventions that incorporate religious conditionality, offering potential to improve poverty alleviation and human capital development. Future research should explore the impact of religious conditionality on CCT outcomes to further enhance the effectiveness of such programs